Sluggish Cognitive Tempo in Pediatric Sickle Cell Disease - Hardy, Steven J.; Forman, Sydney; Hardy, Kristina K.; Schatz, Jeffrey (Frontiers in Neurology, 2022)
Background: Sickle cell disease (SCD) imparts risk for a range of neurodevelopmental and neurocognitive disorders. Sluggish cognitive tempo (SCT) is a distinct syndrome that often co-occurs with attention-deficit/hyperactivity disorder (ADHD) but has not been described in SCD. We investigated the reliability and validity of a SCT measure in SCD and examined associations with biopsychosocial risk factors and functional outcomes. Materials and Methods: Caregivers (n = 85) of children with SCD ages 7-16 reported on socio-demographics and the Kiddie-Sluggish Cognitive Tempo (K-SCT) measure, Behavior Rating Inventory of Executive Function, and Conners 3. Disease-related characteristics were extracted from health records. Results: The K-SCT demonstrated excellent internal consistency (α = .92) and test-retest reliability (r = .82, p < .001). K-SCT scores were correlated with ADHD-Inattention (r = .64, p < .001) and ADHD-Hyperactive/Impulsive (r= .46, p < .001) scores, as well as functional outcomes, including learning problems (r = .69, p < .001). In multivariate analyses controlling for ADHD symptoms, SCT accounted for unique variance in learning (b = 9.67, p < .01) and executive functioning (b = 5.93, p < .01). Nearly all participants (93%) with elevated levels of co-occurring SCT and ADHD-Inattention symptoms had significant learning problems. Conclusion: The K-SCT is a reliable and valid measure of SCT in SCD. SCT symptoms are associated with learning difficulties even after controlling for ADHD symptoms. Further research is needed to understand the biopsychosocial factors that lead to SCT symptoms in SCD and examine long-term implications of SCT.